2019
DOI: 10.1108/ecam-04-2018-0161
|View full text |Cite
|
Sign up to set email alerts
|

APRT-FMEA buffer sizing method in scheduling of a wind farm construction project

Abstract: Purpose The purpose of this paper is to present an efficient model for project buffer sizing by taking failure mode and effects analysis (FMEA) into account to reach a more realistic schedule. Design/methodology/approach In the first phase of the project, several turbines were installed according to the primary schedule with an average duration of 142 days. Then, some of critical chain project management algorithms were separately applied in the implementation and installation of the other wind turbines. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In order to evaluate the proposed algorithm, the inputs from this project were run through several algorithms recently presented, and the obtained results are presented in Table 7 for the sake of comparison. According to the results shown above, the planned project buffer using the proposed algorithm was 13% less than the APRT-FMEA buffer sizing algorithm used by Zohrehvandi and Khalilzadeh [16]. Moreover, the results of implementing the proposed algorithm showed that the planned project buffer was 6% lower compared to the buffer sizing algorithm presented by et al [18].…”
Section: Findings and Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In order to evaluate the proposed algorithm, the inputs from this project were run through several algorithms recently presented, and the obtained results are presented in Table 7 for the sake of comparison. According to the results shown above, the planned project buffer using the proposed algorithm was 13% less than the APRT-FMEA buffer sizing algorithm used by Zohrehvandi and Khalilzadeh [16]. Moreover, the results of implementing the proposed algorithm showed that the planned project buffer was 6% lower compared to the buffer sizing algorithm presented by et al [18].…”
Section: Findings and Resultsmentioning
confidence: 71%
“…Zohrehvandi and Khalilzadeh [16] presented an efficient algorithm for project buffer sizing by taking failure mode and effects analysis (FMEA) into account and reached a more realistic schedule. The proposed algorithm was implemented on a real wind farm construction project.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bakry et al (2016) introduced a buffer sizing algorithm to optimize project planning under uncertainty conditions. Zohrehvandi and Khalilzadeh (2019) integrated the APRT method with Failure Modes and Effects Analysis (FMEA), which resulted in a shorter project duration. Zarghami et al (2019) presented a new step towards the sizing of buffers for CCPM by developing a probabilistic measure obtained through a reliability analysis of project resources.…”
Section: Traditional Buffer Management Methodsmentioning
confidence: 99%
“…They aimed at developing an enhanced critical chain project management framework for effective implementation of construction projects. Zohrehvandi and Khalilzadeh (2019) presented an efficient model for project buffer sizing by taking failure mode and effects analysis into account to reach a more realistic schedule. Vanhoucke (2016) examined the traditional buffer sizing methods and how they are obtained and compared the results through an example.…”
Section: Literature Reviewmentioning
confidence: 99%